(untitled) (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
One of the key segments of a company’s strategic management is managing its growth. Growth needs to be sustainable so that companies can benefit strategically from it. The rate of sustainable growth represents the maximum rate of increase in sales of the company without the need for additional financial resources. The paper will research the key determinants of the sustainable growth rate of 81 companies operating in the Balkan countries in the period from 2014 to 2020. The appropriate statistical methods will research the impact of liquidity, profitability, indebtedness, firm size and asset efficiency on a company’s sustainable growth rate. The obtained results should provide guidelines for the growth rate of the observed companies in the long run, considering that this is an indicator that leads to the growth of the company’s value and meeting strategic goals. Also, the obtained results should indicate how it is possible to ensure long-term profitable and sustainable company growth in a rapidly changing economic, political and competitive environment, and what internal and external incentives are needed to further increase growth potential.